Sustainable controlling of hydrophilic properties of cotton and linen by application of amino acids. Issue 3 (4th March 2017) - Grethe, Thomas; Kick, Thomas; Mahltig, Boris
Abstract : Three different hydrophobic amino acids (valine, leucine, and phenylalanine) are used in wet-finishing application on natural fiber fabrics from cotton and linen. By this application, a decrease in hydrophilic properties of the fabrics can be determined by two analytical methods (capillary rise test and TEGEWA drop test) – with most significant results after application of valine or leucine. By this simple approach, the proof of concept is done that small and natural based molecules can be used for an eco-friendly modification of natural fibers. This could be a promising starting point for further development of eco-friendly finishing agents.